Memory and trauma in international relations theories, cases, and debates - Resende, Erica Simone Almeida; Budryte, Dovile (Interventions, 2014)
"This work seeks to provide a comprehensive and accessible survey of the international dimension of trauma and memory and its manifestations in various cultural contexts"--